HUBUNGAN POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN KEMAMPUAN DASAR ANAK USIA PRA SEKOLAH (3-5 TAHUN) DI DESA CIKANDE TAHUN 2021 - Damayanti, Ivty; Sari, Cucuk Kunang; Sari, Rina Puspita (Nusantara Hasana Journal, 2022)
Preschool is a period in a child's development, in essence not all children can go through a period of growth and development ideally, therefore children encounter disturbances in the process of growth and development and various other conditions. his ageThe research method used in this research is descriptive correlation then the researcher uses a cross-sectional approach. Sampling was carried out by purposive sampling based on data in Cikande Village, Serang Regency in 2021, so that 145 respondents were obtained. The data analysis technique used is the chi square test using SPSS 25.The results of the study found that respondents who had good parenting were 112 people (77.2%) while for respondents who had poor parenting were 33 people (22.8%) and who experienced appropriate child development were 74 people ( 51.0%) while for respondents who experienced inappropriate child development as many as 71 people (49.0%). Chi square test results It was found that there was a relationship between parenting patterns and the development of basic abilities of pre-school age children in Cikande village because the p-value obtained was 0.000 < (0.05)It is hoped for health workers to always check the development of children through early detection or DDTK (Early Detection of Growth and Development) , and provide counseling or counseling on parenting patterns.